The Southern version of Cursor Mundi. - J. Stauffenberg, Henry,Stauffenberg, Henry J. (University of Ottawa Press, 1985)
The medieval poem Cursor Mundi is a biblical verse account of the history of the world, offering a chronological overview of salvation history from Creation to Doomsday. Originating in northern England around the year 1300, the poem was frequently copied in the north before appearing in a southern version in substantially altered form. Although it is a storehouse of popular medieval biblical lore and a fascinating study in the eclectic use of more than a dozen sources, the poem has until now attracted little scholarly attention. This five-part collaborative edition presents the Arundel version of the poem with variants from three others.
Includes bibliographies.
Keywords: medieval poetry; northern england; Cégep du Vieux Montréal; Cursor Mundi; Fish measurement; Jesus; Lorde; Physiker; Time in Indonesia; Tusya language; Watir; WELE; World history; Christian poetry; English (Middle)